2012
DOI: 10.1111/j.1533-2500.2012.00601.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Research Quality of Telehealth Trials in Pain Management: A Meta‐Analysis

Abstract: Although telehealth-based pain management research has grown over the last decade, it is difficult to determine the state of the research because of methodological differences and variability in quality among existing studies. In a previous systematic review, we outlined these differences and preliminarily explored the promise of telehealth for pain intervention. We completed a PRISMA compliant meta-analysis of telehealth pain management research to more precisely describe the state of the research and to unco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…Pooled analyses were performed in 4 reviews and presented subsequently [22-24,27]. One review on chronic obstructive pulmonary disease (COPD) demonstrated the capacity of eHealth interventions to significantly reduce the number of patients with 1 or more emergency department visits or hospital admissions-due to exacerbation of pulmonary symptoms-over a 12-month period [23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pooled analyses were performed in 4 reviews and presented subsequently [22-24,27]. One review on chronic obstructive pulmonary disease (COPD) demonstrated the capacity of eHealth interventions to significantly reduce the number of patients with 1 or more emergency department visits or hospital admissions-due to exacerbation of pulmonary symptoms-over a 12-month period [23].…”
Section: Resultsmentioning
confidence: 99%
“…Because the interventions were often part of complex interventions, the authors concluded that further investigation is required to determine the precise role of eHealth. Promising effects were also identified for Internet-based peer and clinical visit support programs—among several other eHealth interventions—in acute and chronic pain management [18,22]. Although the Internet was supportive in the treatment of pain, it remained unclear what benefits could be gained and which patients would profit most.…”
Section: Resultsmentioning
confidence: 99%
“…Non-compliance may arise if the telehealth programme is too demanding or timeconsuming [28]. It may also arise because of poor usability.…”
Section: Compliance and Usabilitymentioning
confidence: 96%
“…This is significant as the authors note that unpublished material could have provided additional insights. 352 Although Peeters et al 354 supply funding details, they do not specifically report any conflict of interest. For Conway et al's 342 subanalysis, full search terms, the inclusion of unpublished literature and list of excluded studies, and in-depth risk and publication assessments were appraised in the original systematic review and meta-analysis publication.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Although McGeary et al 352 searched for grey literature, they excluded it later without giving any reasons. This is significant as the authors note that unpublished material could have provided additional insights.…”
Section: Quality Assessmentmentioning
confidence: 99%